2019
DOI: 10.2196/12469
|View full text |Cite
|
Sign up to set email alerts
|

Interruptive Versus Noninterruptive Clinical Decision Support: Usability Study

Abstract: Background Clinical decision support (CDS) has been shown to improve compliance with evidence-based care, but its impact is often diminished because of issues such as poor usability, insufficient integration into workflow, and alert fatigue. Noninterruptive CDS may be less subject to alert fatigue, but there has been little assessment of its usability. Objective This study aimed to study the usability of interruptive and noninterruptive versions of a CDS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 29 publications
3
30
0
Order By: Relevance
“…The 75 non-review, non-opinion articles used a variety of metrics to evaluate the usability and acceptability of their CDS tools, with many using more than one metric. The most common evaluation was via interviews (n=29) 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 , followed by surveys or questionnaires (n=16) 27 29 50 53 55 56 57 58 59 60 61 62 63 64 65 66 . Other qualitative feedback responses were obtained by focus groups or workshops (n=5) 43 57 61 67 68 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 75 non-review, non-opinion articles used a variety of metrics to evaluate the usability and acceptability of their CDS tools, with many using more than one metric. The most common evaluation was via interviews (n=29) 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 , followed by surveys or questionnaires (n=16) 27 29 50 53 55 56 57 58 59 60 61 62 63 64 65 66 . Other qualitative feedback responses were obtained by focus groups or workshops (n=5) 43 57 61 67 68 .…”
Section: Resultsmentioning
confidence: 99%
“…One study of a CDS tool for deprescribing found that only 1.2% of alerts resulted in medication discontinuation, which was overall branded ineffective [45]. Another study compared interruptive vs. non-interruptive alerts for ACE inhibitor prescription, finding that the non-interruptive alerts were less annoying but less seen [51]. Unintended consequences should be assessed in addition to expected outcomes [59].…”
Section: Ends Justify the Means -Measuring Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially in CDSS, the evaluation of usability plays a decisive role. Usability refers to the quality of a system, which allows users to complete a task effectively, fast, and with high satisfaction [ 22 ]. While many studies propose methods to improve the performance and accuracy of diagnostic CDSS, to our knowledge, there is no study available that focuses on the design of a CDSS for RDs [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Especially in CDSS, the evaluation of usability plays a decisive role. Usability refers to the quality of a system, which allows users to complete a task effectively, fast and with a high satisfaction [22]. To our knowledge, there is no study available that has assessed a CDSS for RDs regarding the usability and the acceptance by the users.…”
Section: One Of These Use Cases Is a Prototypical Conception And Implmentioning
confidence: 99%